Model Discovery Learning Berbasis Contextual Approach Untuk Meningkatkan Pemahaman Konsep dan Disposisi Matematis Siswa - Afzaun Najwa, Harum; Satria Mukti, Taufiq (Cetta: Jurnal Ilmu Pendidikan, 2025)
Insufficient conceptual comprehension and dispositional capabilities from repetitive and non-innovative instructional methodologies. Overcoming this requires the implementation of strategies to improve student competence. This investigation aims to evaluate the efficacy of a discovery learning with contextual approaches for augmenting students conceptual understanding and mathematical disposition. The research was conducted at SMPN 1 Sumbergempol using a quasi experimental approach the pretest posttest control group design. The sample was taken using purposive sampling based similarity of teachers and homogeneity of class ability. Data is collected through tests measuring understanding of concepts and questionnaires students mathematical disposition. The hypothesis tested using Mann-Whitney analysis. Analytical examination revealed differences in posttest results in conceptual understanding and mathematical disposition in the experimental and control classes, at by a Sig. (2-tailed) value of 0.00 < 0.05. Effectiveness was measured through the N-Gain metric, with the experiment participants achieving an N-Gain coefficient of 0.56 (medium category), while control subjects only achieved 0.29 (low category). For the mathematical disposition, the experiment participants showed an N-Gain coefficient of 0.41 (medium category), while the control subjects showed a coefficient of 0.20 (low category). The conclusion in this study is that there is a difference in the improvement of students conceptual understanding and mathematical disposition between the discovery learning model based on the contextual approach and the expository learning model, the increase in conceptual understanding and mathematical disposition of students who receive the discovery learning model based on the contextual approach is better than students with the expository learning model.